Penerapan Model, Prinsip, dan Elemen Total Quality Management (TQM) di MTSN 1 Surakarta - Epitasari Dwi Purwanti; Gita Salsabila; Fetty Ernawati (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) in Islamic education management at MTsN 1 Surakarta. The focus of the study includes the application of TQM models, principles, and elements, the implementation of educational digitalization, stakeholder involvement, and the strengthening of quality culture in improving educational quality. This research employed a qualitative approach with data collection techniques through observation and interviews. The results of the study indicate that MTsN 1 Surakarta has systematically implemented quality-based management through the stages of planning, implementation, evaluation, and follow-up. The involvement of stakeholders such as teachers, parents, school committees, and the community has contributed positively to improving the quality of education. The madrasah also develops a quality culture through teacher competency development and digital-based flagship programs. In facing challenges related to technological adaptation and service quality improvement, MTsN 1 Surakarta continues to carry out innovation and continuous evaluation in order to realize quality and competitive education